Extrahepatic cholangiocarcinoma in an adult Black Howler Monkey (Primates: Atelidae) - De Santi, Mariele [UNESP]; Do Couto, Caroline [UNESP]; Montanhim, Gabriel Luiz [UNESP]; Moraes, Paola Castro [UNESP]; Bertolo, Paulo Henrique Leal [UNESP]; De Oliveira Vasconcelos, Rosemeri [UNESP]; Coutinho, Acácia Rebello [UNESP]; Werther, Karin [UNESP] (Revista Brasileira de Medicina Veterinaria, 2019)
Over the past years, the number of cases of neoplasms reported in nonhuman primates has increased considerably, with hepatocellular tumors observed in several species. Here, a case of extrahepatic cholangiocarcinoma in an adult male Black Howler Monkey (Alouatta caraya) is presented. The animal, kept as a pet, was admitted to the Veterinary Hospital with clinical signs of cholestasis. After unsuccessful medical treatment, the animal was submitted to a cholecystoduodenostomy. During the surgical procedure, the hepatobiliary system was meticulously observed. The liver showed no macroscopic alterations; however, there was a solid mass throughout the common bile duct. Biopsy specimens were collected from the bile duct mass, liver, and gallbladder for histological and immunohistochemical evaluation. Histological examination of the liver showed diffuse accentuated vacuolization and necrosis, besides hemosiderin accumulation inside hepatocytes. In the portal region, there was an accentuated proliferation of biliary ducts, which were replete with bilirubin. Discrete, neutrophilic, inflammatory infiltrates and fibrosis were also observed. The bile duct mass showed a cellular proliferation of epithelial origin, confirmed on immunohistochemical analysis. The arrangement, characteristics, and growth pattern of these cells revealed a malignant neoplasm. Despite the success of the procedure, the animal died hours later. Cholangiocarcinoma generally presents with a high mortality rate, since its late clinical presentation makes therapy ineffective due to its large extension at the time of diagnosis. The owner did not allow a necropsy; therefore, the presence of other neoplasms and important organ alterations, which may be aggravated the patient's clinical condition, were not confirmed.
Keywords: Alouatta caraya; Cholecystoenterostomy; Histopathology; Immunohistochemistry; Neoplasm